Role of TRPV3 in immune response to development of dermatitis - Hirasawa Tsutomu; Yoshioka Takeshi; Imura Kinichi; Sakata Tsuneaki (BMC, 2009)
Abstract Background Recently, it has been reported that the Gly573Ser substitution of transient receptor potential V3 (TRPV3) leads to increased ion-channel activity in keratinocytes. Our previous studies have indicated that the spontaneous hairless and dermatitis phenotypes of DS-Nh mice, which were newly established as an animal model of atopic dermatitis (AD), are caused by TRPV3Gly573Ser. Although this substitution causes hairlessness in several kinds of rodents, in our investigations, dermatitis developed in only a few animals. Here, we generated NC/Nga-Nh mice to elucidate the role of TRPV3Gly573Ser in NC/Nga mice, which is one of the most studied animal models of AD. Methods To establish and validate the new AD animal model, NC/Nga-Nh mice were generated using NC/Nga and DS-Nh mice, and their clinical features were compared. Next, T-cell receptor (TCR) Vβ usage in splenocytes, evaluation of bacterial colonization, and serological and histological analyses were carried out. Finally, repeated-hapten-application dermatitis was induced in these mice. Results NC/Nga-Nh mice did not develop spontaneous dermatitis, whereas DS-Nh mice displayed this phenotype when maintained under the same conditions. Serological analysis indicated that there really was a phenotypic difference between these mice, and TCR repertoire analysis indicated that TCRVβ haplotypes played an important role in the development of dermatitis. Artificial dermatitis developed in DS and NC/Nga-Nh mice, but not in DS-Nh and NC/Nga mice. Histological and serological analyses indicated that mouse strains were listed in descending order of number of skin mast cells: DS-Nh > DS ≈ NC/Nga-Nh > NC/Nga, and serum IgE levels were increased after 2,4,6 trinitrochlorobenzene application in these mice. Serum IgE level in DS-Nh mice was lower than that mesured in other strains. Conclusion Our results confirm the contribution of the TRPV3Gly573Ser gene to the development of repeated hapten dermatitis, but not spontaneous dermatitis in NC/Nga mice.